Desorption of fructose from a packed column to an oleic acid/fructose oleate mixture for employment in a bioreactor system - Pyo, Sang-Hyun ; 0000-0002-5037-2748; Hayes, Douglas G. (JAOCS, Journal of the American Oil Chemists' Society, 2008)
Adsorption isotherms for a packed column consisting of fructose and silica gel in contact with a liquid phase consisting of oleic acid and fructose mono- and di-oleate at 65 °C were determined to assist the column’s utilization in a bioreactor system for the solvent-free lipase-catalyzed synthesis of saccharide ester biosurfactants. The liquid-phase fructose content was very low, ranging from 0.005 to 0.1% (w/w), with the higher values obtained for a higher fructose concentration in the column and a higher ester content in the liquid phase. The desorption behavior of fructose followed the Freundlich isotherm. An increase in the liquid phase space velocity increased the initial rate of fructose desorption linearly. Dynamic light scattering measurements demonstrate solutions obtained by mechanical stirring of crystalline fructose and oleic acid/fructose oleate contained 50–250 μm sized aggregates, even after centrifugation …